2021
DOI: 10.1080/19475705.2021.1920480
|View full text |Cite
|
Sign up to set email alerts
|

Detection of areas prone to flood risk using state-of-the-art machine learning models

Abstract: The present study aims to evaluate the susceptibility to floods in the river basin of Buzau in Romania through the following 6 machine learning models: Support Vector Machine (SVM), J48 decision tree, Adaptive Neuro-Fuzzy Inference System (ANFIS), Random Forest (RF), Artificial Neural Network (ANN) and Alternating Decision Tree (ADT). In the first stage of the study, an inventory of the areas affected by floods was made in the study area, and a number of 205 flood points were identified. Further, 12 flood pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 97 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…The result of the Boruta method found that fourteen factors were the most important (Rank 1) for the current study, namely, elevation, landform, soil moisture, slope, TRI, LULC, NDVI, NDFI, distance to stream, rainfall, population density, GHMTS, distance to road, and geology (Figure 4a). In contrast, SPI, TWI, and soil erosion had a moderate (Rank 2) influence on flood events, whereas drainage density, profile curvature, TPI, soil type, and aspect had the least importance (Ranks 3, 4, 5, 6, and 7) for FHZ [19].…”
Section: Multicollinearity Test and Boruta Feature Rankingmentioning
confidence: 88%
See 1 more Smart Citation
“…The result of the Boruta method found that fourteen factors were the most important (Rank 1) for the current study, namely, elevation, landform, soil moisture, slope, TRI, LULC, NDVI, NDFI, distance to stream, rainfall, population density, GHMTS, distance to road, and geology (Figure 4a). In contrast, SPI, TWI, and soil erosion had a moderate (Rank 2) influence on flood events, whereas drainage density, profile curvature, TPI, soil type, and aspect had the least importance (Ranks 3, 4, 5, 6, and 7) for FHZ [19].…”
Section: Multicollinearity Test and Boruta Feature Rankingmentioning
confidence: 88%
“…The machine learning (ML) technique is a type of artificial intelligence where prediction is more accurate by using historical data and records. FHZ mapping can be enriched by using various machine learning models, namely, random forest [15], support vector machine [16], extreme gradient boosting [17], classification and regression tree [18], alternating decision tree [19], optimized tree [20], artificial neural network [21], naïve Bayes [22], genetic algorithm rule-set production [23], Bayesian additive regression tree [24], grid search algorithm [25], logistic regression [26], etc. Recently, the novel ensemble-based machine learning (ML) technique was utilized for parallel high computing performance of flood risk zone mapping on a real-time basis.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such problems, machine learning (ML) techniques (e.g., group method of data handling (GMDH), artificial neural networks (ANNs), Naïve Bayes Trees (NBT), support vector regression (SVR), and random forest (RF)) have been posed in the literature (Band et al, 2020;Costache et al, 2021;Dodangeh et al, 2020;Khoirunisa et al, 2021;Khosravi et al, 2018). However, machine learning techniques also suffer from strict parameters tuning procedure which is time-consuming for modelers (Chen et al, 2019(Chen et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…As the amount of flood organization is much higher in the plains and floodplain areas, methods and statistics on flood vulnerability, risk analysis, and mapping are essential to analyze the flood susceptible character of those areas. These methods include Analytical Hierarchy Process (AHP) (Goumrasa et al 2021) as an expert knowledge-based model, Frequency ratio (FR) (Sarkar and Mondal 2020), Information value (IV) (Ul Moazzam et al 2020), Certainly factor (CF) (Cao et al 2020), Logistic regression (LR) (Fustos et al 2017), Weights ofevidence (WOE) (Tehrany et al 2017), fuzzy logic (Perera and Lahat 2015), neuro-fuzzy logic (Kambalimath and Deka 2020) as expert-based models; Artificial neural network (ANN) (Pham et al 2020), Adaptive neuro-fuzz inference system (ANFIS) (Samantaray et al 2021), Decision tree (DT) (Khosravi et al 2021), Support vector machine (SVM) (Costache et al 2021), Random Forest (RF) (Chen et al 2020) as a machine learning model. Hydraulic engineering centre-river analysis system (HEC-RAS) (Namara et al 2021) and soil water assessment tool (SWAT) (Nasir et al 2020) models are also used as hydrological models for determining flood vulnerability and risk.…”
mentioning
confidence: 99%
“…ML-based models can accurately measure the nature and severity of other natural disasters, including flood susceptibility (Bui et al 2020;Rahaman et al 2019). Popular ML models for determining flood susceptibility in an area are Artificial neural network (ANN) (Pham et al 2020), Adaptive neuro-fuzz inference system (ANFIS) (Samantaray et al 2021), Decision tree (DT) (Khosravi et al 2021), Support vector machine (SVM) (Costache et al 2021), Random Forest (RF) (Chen et al 2020) and Extreme gradient boosting (XGBoost) (Ni et al 2020). These methods give an accurate idea of the future flooding of a region.…”
mentioning
confidence: 99%